Primary synovial sarcoma of the mediastinum: a poor prognosis in a 14‐year‐old girl. Issue 8 (8th July 2021) - Saad, Asma; Bouacida, Imen; Ben Radhia, Bechir; Zribi, Hazem; Dridi, Amira; Marghli, Adel
Abstract: Synovial sarcoma is a soft tissue sarcoma. Its occurrence as a primary mediastinal neoplasm is very rare. We report a case of mediastinal synovial sarcoma in a 14‐year‐old girl with exertive dyspnoea at presentation. On physical examination, there was a superior vena cava syndrome and café‐au‐lait spots. Chest X‐ray revealed a white left hemithorax with mediastinal deviation to the opposite side. Thoraco‐abdomino‐pelvic scanner showed a voluminous posterior cervico‐mediastinal tissue mass. Computed tomography (CT)‐guided biopsy of the mediastino‐pleural mass was performed. Histological examination reported fusocellular malignant mesenchymal proliferation. A complementary immunohistological study with a broad range of antibodies was performed with a high‐grade single‐phase spindle cell synovial sarcoma of the mediastinum. She presented a respiratory distress, did not respond to resuscitation, and died. Mediastinal synovial sarcoma is a rare tumour that is difficult to diagnose. Its slow progression and delay in diagnosis may lead to a fatal evolution. Abstract : Synovial sarcoma is a soft tissue sarcoma. Its occurrence as a primary mediastinal neoplasm is very rare. We report a fatal case of mediastinal synovial sarcoma in a 14‐year‐old girl with exertive dyspnoea at presentation. We highlight the role of imaging, the means of diagnosis, and the importance of the speed of therapeutic management. Mediastinal synovial sarcoma is a rare tumour that is difficult to diagnose. Its slow progression and delay in diagnosis may lead to a fatal evolution.